1973
DOI: 10.2307/279150
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution and Development of Fremont Maize Agriculture: Some Preliminary Interpretations

Abstract: This study concentrates upon the distribution and possible developmental sequence of maize agriculture in the northern Southwest, and its significance for Fremont cultural dynamics. Attention is focused upon the corn known as Fremont Dent, which was one of the main forms of maize raised by the peoples of the Fremont culture. Of particular interest is maize material from the Evans Mound, Grantsville, and Nine Mile Canyon Fremont sites, which demonstrates a pattern of regional distribution within the Fremont cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1974
1974
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Fremont groups can be distinguished from the Anasazi by a complex of archaeological traits, including moccasin and pottery style (Fremont "Gray Ware": Madsen, 1977;Jennings, 1978), unique anthropomorphic clay figurines (Morss, 1931;Madsen, 1977), a geographically constrained and drought resistant type of maize ("Fremont Dent": Winter, 1973;Jennings, 1978), and the lack of a formal kiva (Wormington, 1955;Madsen, 1979). The Fremont remained in pit-houses long after Anasazi groups began to live in above-ground structures and probably never developed the complex political and social stratification evidenced at many later Anasazi sites (Frisbie, 1978;Toll, 1991;Sebastian, 1992;Tainter and Plog, 1994).…”
Section: The Fremontmentioning
confidence: 99%
“…Fremont groups can be distinguished from the Anasazi by a complex of archaeological traits, including moccasin and pottery style (Fremont "Gray Ware": Madsen, 1977;Jennings, 1978), unique anthropomorphic clay figurines (Morss, 1931;Madsen, 1977), a geographically constrained and drought resistant type of maize ("Fremont Dent": Winter, 1973;Jennings, 1978), and the lack of a formal kiva (Wormington, 1955;Madsen, 1979). The Fremont remained in pit-houses long after Anasazi groups began to live in above-ground structures and probably never developed the complex political and social stratification evidenced at many later Anasazi sites (Frisbie, 1978;Toll, 1991;Sebastian, 1992;Tainter and Plog, 1994).…”
Section: The Fremontmentioning
confidence: 99%
“…Several different quantitative techniques and data were used to analyze and [91,1989) compare the Elsinore corn (Bird and Bird 1980;Cutler 1961;Cutler and Meyer 1965;Galinat 1985;Nickerson 1953;Wellhausen et al 1952;Winter 1973;Winter and Wylie 1974), but none was shown to be satisfactory due to inconsistencies in published methods of analysis (Wilde and Newman 1988). Subjective comparisons with published photos were also inconclusive, since the Elsinore corn is similar to Basketmaker cobs from Step House (Cutler and Meyer 1965) and Chapalote in level 2 of Clydes Cavern (Winter and Wylie 1974).…”
Section: Corn Remainsmentioning
confidence: 99%
“…This pattern may have been repeated in many areas as expanding farming groups moved west and north from over-populated centers, eventually influencing central Utah. Evidence for contact between central Utah foragers and Basketmaker groups includes Archaic and Basketmaker II materials from Cowboy Caves (Jennings 1975), Anasazi basketry in Clydes Cavern (Winter and Wylie 1974), possible Basketmaker occupation sites in the Waterhold Flat area (Gunnerson 1969), the Rasmussen Basketmaker burial cave in Nine Mile Canyon (Gunnerson 1969), and Fremont-like maize in southern Utah Basketmaker caves (Winter 1973). Large-scale Basketmaker "migrations" probably did not occur, but small parties of farmers from the south may have moved northward into areas which had previously supported only a limited population of foragers.…”
Section: Demographymentioning
confidence: 99%
“…(Martin and Schoenwetter 1960;Irwin-Williams and Tompkins 1968;Irwin-Williams and Irwin 1966;Jennings 1975). Corn farming finally reached the San Juan drainage at about A.D. 46-380 (Jones and Fonner 1954;Lipe 1970;Winter 1973) and central and northern Utah at approximately A.D. 460 (Aikens 1970;Winter 1973). Horticulture continued into the historic period in the economies of the Pueblos, Pima, Papago, Navajo, Apache, River/Upland Yuma, and Southern Paiute, and eventually was adopted by Ute, Goshiute, and Shoshone groups by A.D.…”
mentioning
confidence: 99%